Sustainable development and turkey's biomass energy potential - (:unkn) unknown (IGI Global, 2013)
Although energy is indispensable for the provision of basic human needs and economic growth, it simultaneously threatens the basic elements of life when its production and usage is based on fossil fuels. Scientific evidence proves that high carbon emission is the main reason behind climate change. Therefore, producing energy from more sustainable type of energies has great importance not only to ensure preservation of a clean and livable environment for future generations, but also to reduce high dependence on fossil fuels for the production of energy. The latter issue is particularly important for emerging nations such as Turkey, which do not possess large fossil fuel reserves. Currently, Turkey is in a position to meet less than one third of its energy need domestically. Increasing the share of energy produced from biomass would help to create a low-carbon economy and cleaner environment, and increase the security of the energy supply and reduce dependence on imported oil and gas. The present study focuses on the level of Turkey's biomass energy potential and the way in which to make efficient use of this potential. The chapter forwards two main questions: (1) To what extent can the quality of environment be improved via biomass energy? (2) What changes occur in economic variables such as foreign trade, employment, and balance of payments when fossil fuel is substituted with biomass energy? © 2014 by IGI Global. All rights reserved.